Identification of different Ikaros cDNA transcripts in Philadelphia-positive adult acute lymphoblastic leukemia by a high-throughput capillary electrophoresis sizing method - Ilaria Iacobucci; Annalisa Lonetti; Daniela Cilloni; Francesca Messa; Anna Ferrari; Roberta Zuntini; Simona Ferrari; Emanuela Ottaviani; Francesca Arruga; Stefania Paolini; Cristina Papayannidis; Pier Paolo Piccaluga; et al. (Haematologica, 2008)
Background Ikaros is the prototypic member of a Kruppel-like zinc finger transcription factor subfamily that is required for normal hematopoietic cell differentiation and proliferation, particularly in the lymphoid lineages. Alternative splicing can generate multiple Ikaros isoforms that lack different numbers of exons and have different functions. Shorter isoforms, which lack the amino-terminal domain that mediates sequence-specific DNA binding, exert a dominant negative effect and inhibit the ability of longer heterodimer partners to bind DNA.Design and Methods In this study, we developed a high-throughput capillary electrophoresis sizing method to detect and quantify different Ikaros cDNA transcripts.Results We demonstrated that Philadelphia chromosome-positive acute lymphoblastic leukemia cells expressed high levels of the non-DNA-binding isoform Ik6 that was generated following IKZF1 genomic deletions (19/46 patients, 41%). Furthermore, a recurring 60 bp insertion immediately upstream of exon 5, at the exon 3/exon 5 junction, was frequently detected in the Ik2 and Ik4 isoforms. This insertion occurred either alone or together with an in-frame ten amino acid deletion that was due to a 30 bp loss at the end of exon 7. Both the alterations are due to the selection of alternative cryptic splice sites and have been suggested to cause impaired DNA-binding activity. Non-DNA-binding isoforms were localized in the cytoplasm whereas the DNA-binding isoforms were localized in the nucleus.Conclusions Our findings demonstrate that both aberrant splicing and genomic deletion leading to different non-DNA-binding Ikaros cDNA transcripts are common features of Philadelphia chromosome-positive acute lymphoblastic leukemia.